2006
DOI: 10.1128/jcm.44.1.251-253.2006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Noninvasive Diagnosis of Visceral Leishmaniasis in India: Comparison of Two Immunochromatographic Strip Tests for Detection of Anti-K39 Antibody

Abstract: Used with blood or serum, a new anti-K39 antibody immunochromatographic strip test (IT-Leish; DiaMed AG) proved sensitive (range, 99 to 100%) and specific (range, 95 to 100%) for the noninvasive serodiagnosis of visceral leishmaniasis in India. Used with serum, the IT-Leish test and the existing Kalazar Detect test (InBios International, Inc.) yielded comparable results for symptomatic infection and identified apparent subclinical infection in 15 to 32% of healthy residents in a region where visceral leishmani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
2
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 20 publications
0
51
2
5
Order By: Relevance
“…Contrary to these results, not any of the serological studies using rK39, a non-specific positive reaction has been reported in controls from nonendemic regions. 4 Although this study was conducted in an endemic area of Bihar, but because of the poor sensitivity and specificity of saliva, it cannot be used in normal clinical practice, notwithstanding an isolated report of extremely high sensitivity ( 99%) and specificity (100%) reported from Patna, 7 which could not be reproduced in this study. …”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Contrary to these results, not any of the serological studies using rK39, a non-specific positive reaction has been reported in controls from nonendemic regions. 4 Although this study was conducted in an endemic area of Bihar, but because of the poor sensitivity and specificity of saliva, it cannot be used in normal clinical practice, notwithstanding an isolated report of extremely high sensitivity ( 99%) and specificity (100%) reported from Patna, 7 which could not be reproduced in this study. …”
Section: Discussioncontrasting
confidence: 43%
“…The presence of antibody in nonendemic controls might be because of subclinical infection or an impending clinical illness. 4 With saliva, about 10% subjects tested positive across the categories of controls despite being negative in serology, and this suggests non-specific binding of antibodies to rK39 antigen. Contrary to these results, not any of the serological studies using rK39, a non-specific positive reaction has been reported in controls from nonendemic regions.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 These two species that cause zoonotic VL are believed to be indistinguishable from each other. 4,5 A subclinical form of the infection develops in most persons exposed to L. infantum and L. donovani , [6][7][8][9] and the proportion of dogs that remain asymptomatic after being exposed to the parasite is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Field diagnosis of VL involves an immunochromatographic strip test (ICT) that detects immunoglobulin G (IgG) antibody to recombinant K39 (rk39), an antigen expressed by leishmanial species that produce VL. rK39 immunochromatographic strip test used with blood or serum proved sensitive (range, 99 to 100%) and specific (range, 95 to 100%) for the noninvasive serodiagnosis of VL in India ( Sundar et al, 2005). The rK39 dipstick is a rapid test for VL with very high sensitivity and moderately high specificity (Chappuis et al, 2003).…”
Section: Introductionmentioning
confidence: 99%